Analysis Of Implementation Of Financial Accounting Standards Without Public Accountability Concerning Presentation Of Cooperative Financial Statements (Case Study On Employee Cooperatives, Dgt Of State Treasury In Jakarta) - Aprianti, Elsa; Yudiana, Yudiana; Nur Rizqi, Muhammad; Faizal, Harun (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
In general in the preparation of the financial statements of the cooperatives should be compiled based on the financial accounting standards entities without public accountability ( SAK – ETAP) in accordance with the regulation no. 12/per/M.KUKM/IX/2015 on guidelines for the general accounting of the cooperatives article 3, paragraph 1. This study was conducted in a cooperative employee of the directorate general of the treasury of the state (KOPPBN), this study aims to determine whether the financial report on the KOPPBN have been applying the Financial Accounting Standards Entities Without Public Accountability (SAK – ETAP) in the preparation of its financial statements. The type of research used is research kulitatif and data from this study were obtained from the report data sisa hasil Usaha (SHU) year 2019 as well as interviews with the manager of the cooperative. Based on the research conducted, the results showed that the cooperative employee of the directorate general of the treasury of the country is not yet fully apply the SAK – ETAP in its financial statements this is because in the financial statements in the cooperative employee of the directorate general of the treasury of the state only covers the balance sheet and the SHU or the income statement. Which should be in SAK – ETAP load 5 statements i.e. balance sheet, cash flow statement, income statement, statement of changes in equity and notes to the financial statements.